Advancements and Future Directions of Dual-Target Chimeric Antigen Receptor T-Cell Therapy in Preclinical and Clinical Studies - Chenyun Zhang; Haizhou Liu (Journal of Immunology Research)
In recent years, chimeric antigen receptor T-cell (CAR-T) therapy has made groundbreaking progress in the treatment of various cancer types, particularly hematological malignancies. In the meantime, various preclinical and clinical studies have extensively explored dual-target CAR-T therapies which can be designed to recognize two antigens simultaneously based on the immunophenotype of tumor cells. Compared with single-target CAR-T approach, dual-target CAR-T therapies demonstrate varying degrees of superior antitumor CAR effects, prevent antigen escape and relapse, reduce on-target off-tumor effects, and ensure durable responses in different types of cancer. These advantages highlight the potential future prospects in this field, showing varying degrees of advancement in preclinical and clinical studies. Herein, we aimed to review different dual-target CAR-T studies conducted on a wide range of tumor models, summarizing the selection of target combinations, the efficacy and safety demonstrated in preclinical and clinical settings, the existing limitations, and the potential future directions of this promising therapeutic strategy.